Financial Management Behavior for E-Wallet Users in Jabodetabek - Febria Nalurita; Farah Margaretha Leon; Muhammad Nisfiannoor (Universitas Trisakti, 2022)
This study aims to investigate the impact of financial knowledge, financial attitudes, and internal locus control on financial management behavior with the moderating role of financial risk tolerance. In addition, to analyze the effect of financial knowledge on financial management behavior mediated by financial attitudes. The data collected comes from e-wallet users in Greater Jakarta therefore the sample obtained was 350. Data collected through surveys, tested through validity and reliability tests. Furthermore, hypothesis testing using Structural Equation Modeling. The findings of this study were financial knowledge, financial attitudes, and internal locus control had a significant influence on financial management behavior. It was also found that financial knowledge had an impact on financial attitudes. Financial risk tolerance significantly moderates the relationship between internal locus control and financial management behavior. In addition, it can be proven that financial attitudes mediate the relationship between financial knowledge and financial management behavior. The implication of this research is to help the public, especially electronic wallet users, to be more responsible in financial management behavior and to be able to make wise decisions in their financial expenditures. Meanwhile, policymakers can be more aggressive in conducting financial education programs for the public so that people have more in-depth financial knowledge, especially when using digital financial applications such as e-wallets that continue to grow.